2016
DOI: 10.1589/jpts.28.747
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an active vibration stimulus according to different shoulder joint angles on functional reach and stability of the shoulder joint

Abstract: [Purpose] The purpose of this study was to analyze the effect of an active vibration stimulus exercise according to shoulder joint angles on functional reach and stability of the shoulder joint. [Subjects and Methods] Thirty healthy male students participated in this study. Upper limb length of each subject was measured to obtain normalized measurement values. The exercise groups were as follows: group I (n=10, shoulder joint angle of 90°), group II (n=10, shoulder joint angle of 130°), and group III (n=10, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Muscle activity was measured using sEMG after bodyblade exercise and there was a significant decrease in SCM and UP and there was a significant increase in SA in this study. This result occurred because vibration stimulus less than 50 Hz produced during bodyblade exercise induced tonic vibration reflex on muscle and tendon activating proprioception feedback10, 17 ) . Lister et al showed that bodyblade training increases sense of position, movement and shoulder joint stability and decreases pain and physical symptoms from shoulder joint instability4 ) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Muscle activity was measured using sEMG after bodyblade exercise and there was a significant decrease in SCM and UP and there was a significant increase in SA in this study. This result occurred because vibration stimulus less than 50 Hz produced during bodyblade exercise induced tonic vibration reflex on muscle and tendon activating proprioception feedback10, 17 ) . Lister et al showed that bodyblade training increases sense of position, movement and shoulder joint stability and decreases pain and physical symptoms from shoulder joint instability4 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Thigpen et al showed that, in comparison with ideal posture, FHP causes SA muscle activity decrease and trapezius overwork during upper extremity evaluation6 ) . SCM, superficial neck muscle, muscle activity should be minimized for FHP improvement10 ) . Muscle activity was measured using sEMG after bodyblade exercise and there was a significant decrease in SCM and UP and there was a significant increase in SA in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations